Community Service of Strengthening Financial Management of Micro Small Medium Enterprises (UMKM) in Pandemic Covid-19 - Bahtiar Effendi; Kurniawan Kurniawan; Lulu Setiawati (CV. Creative Tugu Pena, 2022)
The article provides financial management learning assistance to improve the financial management capabilities of Small and Medium Enterprises. This research uses Asset Based Community (ABCD) that utilize the potential asset of community, either social or infrastructure. Three activities in analyzing the research; introduction, mentoring and evaluation. As for this research method includes: the preparation stage which consists of observation, interviews with village heads, delivery of materials, and material counseling, implementation stage consists of the implementation of seminar activities initiated by the approach and assistance to business actors, the evaluation stage of the evaluation of activities that have been carried out have been done. The results of the activity showed that the ability of the learning mentoring participants increased after this community service activity. Keywords: Community Service Management, Micro Small Medium Enterprises, Financial Management